CLASS MANAGEMENT IN IMPROVING STUDENT LEARNING IN THE MUHAMMAD FAHRI INTEGRATED MIS MEDAN TEMBUNG - Wahyuni, Nur; Salsabila, Audisa (REKOGNISI : Jurnal Pendidikan dan Kependidikan (E-ISSN 2599-2260), 2024)
This research aims to find out how classroom management improves student learning at Muhammad Fahri Integrated MIS, Medan Tembung. Field research was carried out using a descriptive qualitative approach, combining observation and interviews as data collection techniques. The research results show that effective classroom management in Muhammad Fahri Integrated MIS is crucial for creating a conducive and productive learning environment. Teachers play a central role in managing the physical setting of the classroom, student behavior, and the application of innovative learning methods. Close collaboration between teachers, students and parents, supported by the integration of technology and diversification of learning approaches, plays an important role in achieving this goal. This research also identified that active support from school management is key in facilitating an inspiring learning environment and supporting the holistic development of students at Muhammad Fahri Integrated MIS.